Benzothiophene Schiff Bases Disrupt Cytoplasmic Membrane Integrity of Gram-Positive and -Negative Bacteria Cells - Ergueden, Bengue; Luleci, Hatice Buesra; Unver, Yasemin (Pleiades Publishing Ltd, 2024)
Objective: With the molecular formula C8H6S, benzothiophene is an appealing synthon showing a wide range of biological activities such as antifungal, antibacterial, antitumor and anticancer properties. Due to increasing concern about the resistance gained by the microorganisms against existing antimicrobial agents, our group is interested in revealing the cellular target site of these compounds. Methods: As a part of our efforts on determination of effect of antibacterial agents, in this study, we focused on the benzothiophene Schiff bases. Antibacterial activity of bis(benzo[b]thiophene-2-yl)alkylmethanimine derivatives was studied via minimum inhibitory concentration measurements. Results and Discussion: One of the compounds, compound (I) (N,N '-(propane-1,3-diyl)bis(1-(benzo[b]thiophene-2-yl))methanimine), proved to be highly active against both Gram-positives; Staphylococcus aureus, Bacillus subtilis, Enterococcus faecalis, Bacillus cereus; and Gram-negatives Escherichia coli, Pseudomonas aeruginosa, Salmonella enteritidis, Shigella flexneri. In order to reveal the effect of this compound on bacterial cytoplasmic membrane, we measured the extracellular conductivity increase upon treatment. Compound (I), showing high antibacterial activity caused a sudden increase of extracellular conductivity due to ion leakage from bacterial cells. In contrast, inactive benzothiophene derivatives did not cause any conductivity increase. Conclusions: We propose that benzothiophene Schiff base (I) disrupts bacteria cytoplasmic membrane integrity, and this action contributes to its antibacterial activity.
Keywords: Benzothiophene; Escherichia coli; Bacillus subtilis; Staphylococcus aureus; Pseudomonas aeruginosa; antibacterial activity